ANALISIS PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP RETURN ON INVESTMENT PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2013-2019 - Ardian, Rufi; Firdarini, Khoirunisa Cahya (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The main purpose of establishing a company is to get the maximum profit possible. Measurement of the level of profit of a company, can be done by using Return on Investment. This study aims to analyze the effect of the Current Ratio, Total Debt to Assets Ratio, Inventory Turnover, Total Assets Turnover, and Working Capital Turnover on the Return on Investment of retail companies listed on the IDX for the period 2013-2019. This research method is quantitative with 56 research samples taken from eight retail companies multiplied by seven periods. The sampling technique used was purposive sampling. Meanwhile, the data analysis used is statistical descriptive analysis, classical assumption test, multiple linear regression analysis, F statistical test, t statistical test, and coefficient of determination (R2) test. Based on the results of the t statistical test, the results obtained that: 1) Current Ratio has a negative and significant effect on Return on Investment, with a t-count value of -4.377 > t-table value (-2.005) and a significance value of 0.000 <0.05; 2) Total Debt to Assets Ratio has a negative and significant effect on Return on Investment, with a t-count value of -5.561 > t-table value (-2.005) and a significance value of 0.000 < 0.05; 3) Inventory Turnover has a negative and significant effect on Return on Investment, with a t value of -5.893 > t table value (-2.005) and a significance value of 0.000 < 0.05; 4) Total Assets Turnover has a positive and significant effect on Return on Investment, with a t-count value of 2.146 > t-table value (2.005) and a significance value of 0.037 < 0.05; 5) Working Capital Turnover has no significant effect on Return on Investment, with a t value of 0.864 < t table value (2.005) and a significance value of 0.392 > 0.05. Current Ratio, Total Debt to Assets Ratio, Inventory Turnover, Total Assets Turnover, and Working Capital Turnover simultaneously have a significant effect on Return on Investment in retail companies listed on the IDX from 2013 to 2019, with a significant value of 0.000 < 0.05 and calculated F value > F table (12,910 > 2,40). The value of Adjusted R2 is 0.520 or 52%, while the remaining 48% is influenced by other independent variables not examined in this study.